2012
DOI: 10.1155/2012/856029
|View full text |Cite
|
Sign up to set email alerts
|

Dentatin Induces Apoptosis in Prostate Cancer Cells via Bcl-2, Bcl-xL, Survivin Downregulation, Caspase-9, -3/7 Activation, and NF-κB Inhibition

Abstract: This study was set to investigate antiproliferative potential of dentatin (a natural coumarin isolated from Clausena excavata Burm. F) against prostate cancer and to delineate the underlying mechanism of action. Treatment with dentatin dose-dependently inhibited cell growth of PC-3 and LNCaP prostate cancer cell lines, whereas it showed less cytotoxic effects on normal prostate epithelial cell line (RWPE-1). The inhibitory effect of dentatin on prostate cancer cell growth was due to induction of apoptosis as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 48 publications
(54 reference statements)
1
46
0
Order By: Relevance
“…Many of these reports have shown that coumarins up-regulate proapoptotic factors, while they down-regulate anti-apoptotic markers in cancer cells (Arbab et al, 2012;Rubio et al, 2014;Singh et al, 2011), mechanisms that could plausibly apply also to our studied methylcoumarin derivatives. For instance, it has been shown that dentatin, a natural coumarin, induces apoptosis in prostate cancer cells mediated by down-regulation of antiapoptotic proteins (Bcl-2, Bcl-xL, and survivin), disruption of mitochondrial membrane potential, and also NF-kB inhibition (Arbab et al, 2012). In another report, RKS262, a coumarin derivative, has shown to induce apoptosis by reduction of mitochondrial membrane depolarization potential, up-regulation of pro-apoptotic markers (Bid, Bad, and Bok), and down-regulation of pro-survival factors (Bcl-xl and Mcl-1) (Singh et al, 2011).…”
Section: Resultsmentioning
confidence: 53%
“…Many of these reports have shown that coumarins up-regulate proapoptotic factors, while they down-regulate anti-apoptotic markers in cancer cells (Arbab et al, 2012;Rubio et al, 2014;Singh et al, 2011), mechanisms that could plausibly apply also to our studied methylcoumarin derivatives. For instance, it has been shown that dentatin, a natural coumarin, induces apoptosis in prostate cancer cells mediated by down-regulation of antiapoptotic proteins (Bcl-2, Bcl-xL, and survivin), disruption of mitochondrial membrane potential, and also NF-kB inhibition (Arbab et al, 2012). In another report, RKS262, a coumarin derivative, has shown to induce apoptosis by reduction of mitochondrial membrane depolarization potential, up-regulation of pro-apoptotic markers (Bid, Bad, and Bok), and down-regulation of pro-survival factors (Bcl-xl and Mcl-1) (Singh et al, 2011).…”
Section: Resultsmentioning
confidence: 53%
“…BIRC5 is rarely expressed in most terminally differentiated normal tissues but is abundantly and ubiquitously expressed during fetal and embryonic development. Of note, survivin is up-regulated in almost all human malignant tumors and recently has been considered as a diagnostic and prognostic marker for human PCa (35,36). An examination of clinical samples has established that the expression of survivin gradually rises from the low levels observed in normal prostate tissue, through low-grade primary carcinoma, to high-grade primary carcinoma, and is highest in lymph node metastases (15,37).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, their expression has been detected in common tumors, and common inhibitors can bind both proteins (Arbab et al, 2012;Oakes et al, 2012). The similar structure and properties of Bcl2 and Bcl-xL allow to build the Bcl-2 core by including a short loop of Bcl-xL instead of the FLD (PDB: 1GJH and 1G5 M).…”
Section: Identities and Differences Between Bcl-2 And Bcl-xlmentioning
confidence: 99%